Improving nutrition in ACP countries – the role of agriculture - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2011)
Around 1 billion people in the world suffer from hunger, while another 1 billion eat too much of the wrong types of food. The Brussels Development Briefing on ‘Nutrition Security in ACP Countries’ held in June 2011 discussed the measures needed to ensure that agriculture provides the quality and quantity of food required to sustain a healthy population. This CTA Policy Brief covers topics such as food safety and human nutrition, food security, economics and policy. It highlights the need for policy-makers to: learn from the experience of other countries, encourage greater collaboration between the agricultural, health and nutrition sectors, and stimulate small-scale farm production.